DEVELOPMENT OF INNOVATIVE INSURANCE PRODUCTS OF THE FINANCIAL MARKET - Kussainova, A.A.; Kozlowski, Waldemar; Gerashchenko, I.P. (Academic Journal of Physical and Chemical Sciences, 2018)
Innovative insurance products of the financial market are considered. Stages of development of financial insurance derivatives are allocated. Traditional derivative financial insurance instruments - swaps, forwards and the futures which were widely adopted as tools on management and insurance of risks, and nonconventional financial insurance instruments are discussed: the percentage and credit derivatives, forward and option bonds, based on combination of securities and financial transactions. The efficiency of use in activity of the companies of the innovative insurance structured products of the financial market was proved. Opportunities, merits and demerits of traditional and synthetic securitization were analyzed. Possibilities of cryptocurrencies as innovative product of the financial market are discussed. The conclusion is drawn that today the worked concept on use of innovative potential of insurance instruments of the world financial market at strategic modeling of activity of the company is necessary. The strategic modeling which is based on innovative solutions in the field of primary activity of the company is capable to bring optimum results only under the condition of innovative solutions of the primary activity of the company, optimum connected to innovative solutions in the field of strategy hedging by financial derivatives.